The influence of Ross 308 breeder flock age on serum Newcastle Disease Virus and Infectious Bursal Disease Virus antibody levels and their transfer to offspring - Wegner, M.; Gesek, M. (Polish Journal of Veterinary Sciences, 2026)
An effectively immunized parent flock forms the foundation for the proper development of healthy chicks, largely due to the mechanism of vertical transfer of maternal antibodies (MatAb), which provides passive immunity during the early life stages of the chicks. The aim of this study was to evaluate the influence of the age of the Ross 308 parent flock on antibody levels in the serum of the hens and their chicks during the same period with regard to Infectious Bursal Disease (IBD) and Newcastle Disease (ND), as well as to analyses the transfer of antibodies from the hens to their offspring. The study was conducted on a farm with 6500 hens. Blood samples for serological analysis were randomly collected from 84 hens of a single flock and 84 one-day-old chicks hatched from eggs laid by this flock at 30, 40, 50, and 60 weeks of age. In the laboratory, antibody levels in the hens’ blood serum against Newcastle disease virus (NDV) and infectious bursal disease virus (IBDV) were determined using the ELISA test. At the same time, maternal antibody titers (MatAb) in chicks against the same pathogens were measured. The percentage (%) of maternal antibody transfer to the offspring was then assessed. The study demonstrated the impact of parent flock age on antibody levels against the tested pathogens, expressed as geometric mean titers (GMT). During the laying period, GMT values for antibodies against NDV increased with flock age. The highest values were observed at the end of the reproductive period (GMT₆₀=20456), and the lowest at the beginning (GMT₃₀=12631). An opposite trend was observed for IBDV antibodies, whose levels decreased with increasing hen age. The highest values (GMT₃₀=10759) occurred at the beginning of the laying period, and the lowest at its end (GMT₆₀=7421). The highest vertical antibody transfer to offspring was observed for IBDV antibodies (97.7%) at 40 weeks of age, while the lowest was for NDV antibodies (59.7%) at 60 weeks of age. The analysis of results showed significant variation in antibody levels in hen serum during the laying period, as well as in the amount of maternal antibodies transferred to offspring. The obtained data suggest that the effectiveness of passive immunity transfer to chicks is closely related to both the age of the parent flock and the nature of the pathogen targeted by vaccination.